Nontuberculous mycobacteria in patients of a specialty hospital - Barboza, Grazielle Conceição Sousa; Almeida, Isabela Neves de; Santos, Lucas Benício dos; Augusto, Claudio José; Leal, Élida Aparecida; Pádua, Cristiane Aparecida Menezes de; Cesar, Aina Liz Alves; Kritski, Afrânio Lineu; Carvalho, Wânia da Silva; Miranda, Silvana Spíndola de; Figueredo, Lida Jouca de Assis (Revista do Instituto de Medicina Tropical de São Paulo, 2023)
The incidence and clinical characteristics of NTM diseases in Brazil remain relatively unknown. The present study describes the diagnosis of NTM isolates, the clinical presentation and treatment outcomes. We analyzed NTM isolates in patients of a tertiary hospital in the Southeast region of Brazil, from January 2008 to July 2019. The ATS/IDSA criteria for diagnosis and treatment of these patients was applied. Mycobacterium kansasii were identified in 13/113 (11.5%) patients. In 59/113 (52.2%) patients who met the ATS criteria for disease, 29/59 (49.1%) received treatment, and 22/29 (75.8%) were cured. The major species identified was M. kansasii. The most frequent symptoms among the treated patients were dyspnea and cough, and the proportion of cured patients was high.